The protecting group enabled para-selective C–H benzylation of anilides via iron(ii) catalysis: a convenient approach for the synthesis of triarylmethanes. Issue 14 (10th June 2020) - Han, Yi; Li, Guobao; Liu, Lingling; Dai, Chenyang; Shi, Da-Qing; Zhao, Yingsheng
Abstract : We report the para -selective C–H benzylation of phenyl carbamate with an iron(ii ) catalyst. Abstract : We report the para -selective C–H benzylation of phenyl carbamate with an iron(ii ) catalyst. This new method provides an efficient and convenient approach for the synthesis of triarylmethanes starting from readily available anilines and diphenylmethane. Preliminary mechanistic studies revealed that the iron(ii ) catalyst was essential and the use of the sterically demanding isobutoxy group led to high para -selectivity.